Heavy Metals and Safety of Fresh Fruits in Bangalore City, India - A Case Study - Mahdavian, Seyed Esmael; Somashekar, RK (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Urban food security in India is a matter of growing concern. It is estimated that by 2005, 60% of India's population will be living in urban areas. The presence of heavy metals in human body always draws scientific concern as these are considered responsible for affecting health, especially in these days where the release of toxic wastes in the environment has been increased. The increasing trends in food contamination in urban areas are largely attributed to the polluted environment in urban agriculture, contaminated food transport and supply chains; poor market sanitary conditions, and the use of contaminated or waste water for irrigation purposes. The objectives of this paper to measure the levels of heavy metal contamination of fruits in Bangalore markets and assess how the heavy metal contamination might have impacted food safety standards vis a vis heavy metals on urban consumers. The results show that urban consumers are at greater risk of purchasing fresh fruits with high levels of heavy metals beyond the legally permissible limits as defined by the Indian Prevention of Food Adulteration Act, 1954. It must be noted here that these norms are less strict than international food safety norms like Codex Alimentarius or European Union standards. It is therefore suggested here that care should be taken in the following: reduce pollution at water source points; improve post harvest handling; enhance better coordination in fresh crops trading system to improve food safety standards; improve sanitary conditions for the city food markets; and increase awareness in consumers and policy makers on the dangers of heavy metal contamination in the food intake. Keywords: Heavy metals; Prevention of Food Adulteration Act; Atomic Absorption Spectrophotometer (AAS) DOI: 10.3126/kuset.v4i1.2880 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 17-27